COGNITIVE AND CULTURAL SPECIFICITY OF METAPHORS IN ENGLISH AND CHINESE LITERARY DISCOURSE - Nigere Hamiti (International Journal of Literature and Language Studies, 2026)
Abstract. The article examines the cognitive and cultural characteristics of metaphors in English and Chinese literary discourse. Drawing upon Cognitive Metaphor Theory developed by Lakoff and Johnson, the study investigates how metaphorical representations reflect both universal cognitive mechanisms and culture-specific conceptual models. The research analyzes metaphorical expressions selected from English and Chinese literary texts and classifies them according to their cognitive and semantic functions. Particular attention is devoted to ontological, orientational, structural, emotional, symbolic, and anthropomorphic metaphors. The findings demonstrate that while many metaphorical patterns are grounded in shared human experience, their literary realization and symbolic interpretation are significantly influenced by cultural traditions, philosophical beliefs, and national worldviews. English literary metaphors frequently reflect individualistic perspectives shaped by Christian and Humanistic traditions, whereas Chinese literary metaphors reveal concepts of harmony, balance, and interconnectedness associated with Confucian, Daoist, and Buddhist philosophies. The study contributes to contemporary research in cognitive linguistics, literary stylistics, and intercultural communication by highlighting the relationship between metaphor, cognition, and culture.